Juveniles and Their Parents: Narratives of Male & Female Adolescents in Rehabilitation Centres - Abdul Kuthoos, Haja Mydin; Endut, Noraida; Selamat, Nor Hafizah; Mohd Hashim, Intan Hashimah; Azmawati, Azman Azwan (International Digital Organization for Scientific Information, 2016)
A number of studies, internationally, have established a relationship between family structures and environment with juvenile delinquency (Harper and McLanahan, 1998; Larson, Swyers and Larson, 1995; Anderson, 2002). Not many studies have been conducted in Malaysia to link juvenile delinquency with the context of juveniles’ families, especially of their parents or people assuming the role of their parents. This paper is an early attempt at understanding the experiences of juveniles with their parents in order to explore the relationship between their experiences and their involvement in crime or juvenile behaviour. For this purpose, a qualitative research approach was adopted by conducting in-depth interviews with seven (7) male juvenile offenders from a rehabilitation centre in Penang and five (5) female juvenile offenders from a rehabilitation centre in Kedah, Malaysia. The interviews provide an insight into the male and female juveniles’ personal feelings about their experiences and relationships with their parents or persons whom they identify as people have parental guardianship over them. The study finds that adolescents who are involved in delinquencies expressed much unhappiness with their parents due to reasons such as their parents having divorced, not receiving love from their parents, feeling uncared by their parents and families, having strained relationships with their family and experiencing violence from their parents and/ or family. The narratives of the juveniles are hoped to be able to inform us about specific areas to explore further in understanding the criming and delinquent behaviour of juveniles.